Expediency of modification of city transport system by implementation of passenger water transport - Budnyk, Viktoriia; Lernichenko, Kateryna; Korniiko, Yana; Valiavska, Nataliia (Technology audit and production reserves, 2019)
The object of research is the integration of local passenger water transport in the transport system of the city. Among a number of problematic issues, one can single out the unpreparedness of the urban transport infrastructure for the implementation of water transport for the transport of passengers, although this type of transport is an important component of intercity and suburban passenger transport in world megacities located on water arteries. Water transport is characterized and passenger water transport in Ukraine is analyzed. The definition of «transport system» as a whole and separately in part of urban passenger traffic is investigated. The components of the transport system of the city are determined. The structure of the city transport system in Kyiv (Ukraine) is investigated and supplemented with its new subsystem in the element «city passenger transport» – local passenger water transport. Such a structural change makes it possible to qualitatively improve the existing transport supply of cities with water areas, and to offer local residents an alternative mode of transport. Implementation of a new type of urban passenger transport in the transport system of the city requires its detailed study. Therefore, this type of transport is structured, its classification is provided, the concept of «local passenger water transport» and its types are formulated: Water Bus and Water Taxi, which allows to offer them for further use in the scientific environment, in relation to local passenger water transport. As part of the research, it is proposed to identify elements of local passenger water transport, namely: passengers, transport, local passenger transport enterprises, regulatory entities, and local authorities. Each of the elements is proposed to be structured by type. Thanks to this, a modified scheme of the system of urban passenger transport is developed, which provides the basis for the harmonious implementation of this type of transport. The implementation of the proposed changes is justified by the socio-economic significance of this type of transport and the necessary qualitative structural changes in the urban transport system.